2020
DOI: 10.1177/0959353520930602
|View full text |Cite
|
Sign up to set email alerts
|

“The most lonely condition I can imagine”: Psychosocial impacts of endometriosis on women’s identity

Abstract: Endometriosis is a condition which affects around 1–2% of women worldwide and has profound effects on their everyday lives. Previous research has tended to focus on physical symptoms (such as chronic pain); how women manage changes to their identity and relationships as a result of endometriosis has received less attention. This paper discusses qualitative data examining how women negotiate changes to identity while living with endometriosis, in a social context where women are expected to minimise their sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 42 publications
5
36
0
1
Order By: Relevance
“…In addition to pain, women reported that the endometriosis-related experiences that most impacted their lives in a negative way included depression or anxiety (80%), heavy menstrual bleeding (71%), the need to take prescription treatments (57%) or undergo multiple surgeries (49%) or infertility (46%). In other studies, women have reported not feeling ‘normal’ or feminine, experiencing a range of negative emotions (eg, anger, depression, hopelessness, disappointment and exhaustion), having limited physical or sexual activity, struggling to find appropriate treatments, feeling guilt over disrupted relationships and suffering in silence due to endometriosis-related symptoms 22 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pain, women reported that the endometriosis-related experiences that most impacted their lives in a negative way included depression or anxiety (80%), heavy menstrual bleeding (71%), the need to take prescription treatments (57%) or undergo multiple surgeries (49%) or infertility (46%). In other studies, women have reported not feeling ‘normal’ or feminine, experiencing a range of negative emotions (eg, anger, depression, hopelessness, disappointment and exhaustion), having limited physical or sexual activity, struggling to find appropriate treatments, feeling guilt over disrupted relationships and suffering in silence due to endometriosis-related symptoms 22 23…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, few studies have examined the impact of endometriosis on a woman’s life course (ie, ‘life-course impairment’) based on how symptoms and experiences resulting from the disease influence major life events and decisions (such as whether to pursue educational opportunities, choose a career path, establish intimate relationships and plan for a family) and the overall ability of patients to attain their life goals 19 20. The few existing studies have small sample sizes or are qualitative, relying on informational interviews to ascertain the life-course impact of the disease, but highlight the substantial impacts that endometriosis can have on social activities, intimate relationships, education, work productivity and psychological well-being 11 21–23. Understanding life-course impairment, as opposed to focusing on the symptoms of the disease (such as pain or infertility, which are most often addressed individually not holistically), is vital because of the complicated inter-relationship among symptoms and their downstream effects.…”
Section: Introductionmentioning
confidence: 99%
“…This is paired with a current lack of comprehensive clinical guidance for diagnosing and signposting those presenting with endometriosis indicator symptoms, resulting in the label ‘missed disease’ (Overton and Park, 2010). A risk associated with this delayed diagnosis is that patients experience feelings of isolation, especially during crucial periods of identity development during young adulthood (Cole et al, 2021; Marschall et al, 2021). This was particularly evident in participants’ concerns surrounding fertility, with many questioning their role as a woman based on social and cultural expectations.…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly evident in participants’ concerns surrounding fertility, with many questioning their role as a woman based on social and cultural expectations. Recent literature suggests that infertile women with endometriosis struggle to maintain a ‘feminine identity’ (Cole et al, 2021), as well as anxiety and worry surrounding future family planning (Hudson et al, 2016). Participants in this study also emphasised the role of clinicians in fertility-based decision making to provide informed guidance, alongside the emotional support from within their own support network.…”
Section: Discussionmentioning
confidence: 99%
“…Holistic research on diseases like endometriosis is essential, however, because holistic research identifies how an individual lives with their disease on a daily basis and how they plan and prepare for the future. Existing life‐course data on endometriosis suggest that endometriosis significantly affects one's social life, work, education, relationships, and well‐being, 3,4 but larger studies are needed to generalize these findings.…”
Section: Survey Highlights the Significant Toll Of Endometriosis On T...mentioning
confidence: 99%